Epistemologia do desacordo - Silva, Michele Santos da (2012)
People disagree all the time. The objects of discordance vary from the most banal, such as the correct location of a restaurant, to more sophisticated issues understood by some experts, as in the case of the Sciences. The question proposed here is the following: what is the relevancy of the disagreement to the epistemic justification? When one is in total disagreement, should we rethink our doxastic attitude? Initially, I sought for an answer in the form of a single epistemic norm for cases such as these. I will present the currents that have initially proposed such norms and how epistemic variables transform this vision during the deep debate over this issue